Energy harvesting technologies on high-speed railway infrastructure: review and comparative analysis of the potential and practicality - Sun, Wenjing; Thompson, David J.; Yurchenko, Daniil; Zhao, Dong; Luo, Zhenhua; Khan, Irfan (Elsevier, 2025)
A comprehensive quantitative analysis is provided of the potential applications of energy harvesting (EH) technologies tailored to high-speed railway infrastructure. The study compares the various energy sources within railway infrastructure and identifies suitable EH technologies. Feasible designs and scales of EH are assessed based on the installation location; the overall power availability and energy yield are compared for a notional high-speed railway. For resonant EH devices an assessment is also given of the optimal tuning frequency. Vibration-based EH, when applied to the track or bridge structures, can provide sufficient power for individual low-power sensors; however, its output is insufficient for higher-power applications or for data transmission unless energy storage devices are incorporated. Despite the elevated noise levels generated by high-speed trains, the energy available from this acoustic source is negligible and impractical for EH. Small vertical axis wind turbines installed close to the track and driven by passing trains show great potential, capable of harvesting several orders of magnitude more energy than vibration-based EH. Solar photovoltaic panels can generate significantly more energy than other methods, although their output is confined to daylight conditions and is contingent upon weather conditions.
Keywords: Energy harvesting; Railway infrastructure; High-speed rail; Vibration-based harvesting; Wind energy; 4004 Chemical Engineering; 40 Engineering; 4008 Electrical Engineering; 7 Affordable and Clean Energy; 3302 Building